Factors that influencing customer satisfaction towards Melaka River Cruise (MRC) / Nur Faradila Saad - Saad, Nur Faradila (2011)
This research was carried out to identify the factors that influence customer’s satisfaction towards Melaka River Cruise from the customer view point. This study was based on non-probability sampling and convenience sampling design to gather all the information regarding customer’s satisfaction towards Melaka River Cruise (MRC). The data was collected through the distribution of questionnaires. 200 questionnaires were distributed to the respondents in order to get their feedback. After the questionnaire survey was collected and analyzed, the frequency counts and percentage of data were computed. All the data will be compute into Statistical Package for Social Science (SPSS). Using the SPSS, the data collected will be interpret more predict to examine the relationship between dependent variable and independent variables. There are significant and positive relationships between the responsiveness, access and assurance factors with customer satisfaction where majority are agreeing and satisfied with Melaka River Cruise service. The result indicates assurance factor has a strong relationship with customer satisfaction which represent the percentage of 77.8% followed by responsiveness and access factor with 62.4% and 54.9% respectively. Recognizing the problems by Melaka River Cruise will give a general guidance to improve the products and customer service given as well as gaining customer satisfaction while enhance the overall product and service.